STRATEGIC MANAGEMENT OF ENTERPRISE'S INNOVATIVE DEVELOPMENT AS THE BASIS FOR ENSURING ITS COMPETITIVENESS - KAPINOS, Hennadii; LARIONOVA, Katerina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the theoretical and methodological foundations and practical aspects of strategic management of enterprise innovative development as a key factor in ensuring its competitiveness. The relevance of the problem is substantiated in the context of rapid global economy development, intensifying competition, and acceleration of scientific and technological progress.The essence of enterprise innovative development is revealed as a complex continuous process of qualitative changes aimed at systematic renewal of all aspects of activity through the implementation of technological, organizational, marketing, and social innovations.The role and significance of strategic management in ensuring the effectiveness of innovation processes and forming competitive advantages of the enterprise are substantiated. Key elements of strategic management of innovative development are identified, including strategic analysis and planning, organizational support, management of innovative potential and processes, financial support, motivation system, control, and efficiency evaluation.A step-by-step approach to forming a strategic management system for innovative development is proposed, encompassing the preparatory stage, development of management concept, formation of organizational structure, creation of regulatory and methodological framework, resource provision, implementation of management mechanisms, and establishment of monitoring system.The impact of strategic management of innovative development on enterprise competitiveness is investigated through ensuring technological leadership, increasing adaptability to market changes, growing economic efficiency, and strengthening market positions. The comprehensive nature of competitiveness enhancement is analyzed, which manifests in production-technological, market-economic, organizational-managerial, personnel, marketing, financial, information-digital, and environmental spheres of enterprise activity.The synergistic effect from the interaction of various aspects of innovative development in ensuring long-term enterprise competitiveness is substantiated.
Keywords: innovative enterprise development; innovations; strategic management of innovative development; enterprise competitiveness; innovation strategy